Pesantren-Based Vocational Curriculum Management in Improving The Quality of Madrasa Education in Indonesia - Humaisi, M. Syafiq; Thoyib, Muhammad; Alim, Nur (Cendekia: Kependidikan dan Kemasyarakatan, 2022)
This article aims to explain the urgency of pesantren-based vocational curriculum management in improving the quality of madrasa education in the current era of global competition. This research used a qualitative approach and the interactive analysis model of Miles, Huberman, and Saldana to analyze the data. The results of this study confirm some aspects. First, the vocational curriculum planning at MA Nurul Jadid is based on the vision, mission, goals, and educational concepts that rely on a curriculum trilogy, including the madrasa curriculum, skills curriculum, and pesantren curriculum based on the study of the yellow book. Second, implementing the vocational curriculum at MA Nurul Jadid is structured, systematic, and integrated, allowing students to understand and master knowledge and skills proportionally. Third, the evaluation of the vocational curriculum at MA Nurul Jadid Probolinggo is done in a structured, detailed, and comprehensive manner. It is not only on the subject matter but also includes achievements in self-development, extracurricular, organizational, and the formation of national character and culture.